PENERAPAN INTEGRASI SINTAKS INKUIRI DAN STAD (INSTAD) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA KELAS VII-D SMPN 27 SURAKARTA - PRAYITNO, BASKORO ADI; Sugiharto, Bowo; Wahyu, Wahyu (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2013)
Based on our observation to student and discussion with biology teacher of SMPN 27 Surakarta on April 15, 2010, known that there were complicated problems in Biology class VII-D. The core of those problems was most of the students’ ability on higher order thinking was still lower, therefore, in this research we want to try to solve the problems by classroom action research (CAR). Some studies shown that applying syntax of inquiry and STAD model have many advantages to solve this problem. Hence, these models was applied in this school. The research was conducted during 7 months, start from April until November 2010. The research design was Classroom Actions Research by Kemis and Taggart model, which consist of four phases, i.e. planning of action, doing the action, observation, and reflection. The result of this research showed that applying syntax of integrated inquiry and STAD model can improve the student ability on higher order thinking at Biology classes of grade VII SMPN 27 Surakarta.